Uma abordagem histórica da trajetória da parasitologia - Mascarini, Luciene Maura [UNESP] (ABRASCO - Associação Brasileira de Saúde Coletiva, 2003)
The text describe the ways following for the parasitology, a science that emerged in century 19 with the sprouting and the establishment of some areas of the medicine, between them, the tropical medicine. This science in agreement with bibliographical summary was indicated initially as a branch of natural history, being constructed with the discovery and subsequent description of several pathogenic agents responsible for some morbid processes, until then not attributable by external organisms to the individual. Some parasitologists around of the world began to describe, beyond of pathogenic agents, the vectors and the mechanisms of transmission of the several diseases caused by the parasites. In Brazil, the report of the parasitology borders the itinerary of the tropical medicine, with the constant shock between the doctors of the Society of Medicine and Surgery of Rio de Janeiro and Bahian Tropicalista School. Already in 1900, famous doctors parasitologists appear in the Brazilian scene: Oswaldo Cruz and Carlos Chagas that by their discoveries, they stimulated the parasitology until the current days.

O texto relata os caminhos trilhados pela parasitologia, uma ciência que emergiu no século 19 com o surgimento e o estabelecimento de várias áreas da medicina, entre elas, a medicina tropical. Essa ciência, segundo o sumário bibliográfico, foi indicada inicialmente como um ramo da história natural, sendo construída com a descoberta e posterior descrição de vários agentes patogênicos, responsáveis por alguns processos mórbidos, até então não atribuíveis a organismos externos ao indivíduo. Alguns parasitologistas ao redor do mundo começaram a descrever, além dos agentes patogênicos, os vetores e os mecanismos de transmissão das diversas doenças causadas pelos parasitas. No Brasil, o histórico da parasitologia margeia o trajeto da medicina tropical, com o constante embate entre os médicos da Sociedade de Medicina e Cirurgia do Rio de Janeiro e da Escola Tropicalista Baiana. Já em 1900, renomados médicos parasitologistas surgem no cenário brasileiro: Oswaldo Cruz e Carlos Chagas que, através de suas descobertas, impulsionaram a parasitologia até os dias atuais.
A historical approach of the trajectory of the parasitology
Keywords: Historical of the medicine; Parasitology; Tropical medicine; Histórico da medicina; Parasitologia; Medicina tropical